Does Physician-Hospital Vertical Integration Affect Hospital Output? - Soumya Upadhyay; Neeraj Bhandari (Health Services Insights)
Background: Physician-hospital vertical integration is gaining steam but it is unclear how they affect hospital output. Objective: To examine the direct impact of vertical integration on hospital output. Design: A pooled design with 6-year data using linear regressions was used. Then, panel data design with hospital fixed effects was used. Methods: We linked American Hospital Association data (2016-2021) with AHRQ Comparative Health System Performance Initiative’s Compendium (2018, 2020, 2021; 34 987 hospital-year observations) to develop new measures of vertical integration and assess its relationship with several measures of hospital output including annualized total admissions, total number of inpatients days, and total number of emergency department (ED) and outpatient visits. Results: We find that a hospital’s entry into a vertical integration has little or no impact on a broad set of metrics capturing hospital output. Conclusion: Our findings suggest that vertical integrations as currently structured may not yield meaningful gains in output or productivity and hospitals faced with declining productivity need to carefully consider the expected gains from vertical integration strategies.